2016
DOI: 10.7554/elife.17823
|View full text |Cite
|
Sign up to set email alerts
|

Upregulation of neurovascular communication through filamin abrogation promotes ectopic periventricular neurogenesis

Abstract: Neuronal fate-restricted intermediate progenitors (IPs) are derived from the multipotent radial glia (RGs) and serve as the direct precursors for cerebral cortical neurons, but factors that control their neurogenic plasticity remain elusive. Here we report that IPs’ neuron production is enhanced by abrogating filamin function, leading to the generation of periventricular neurons independent of normal neocortical neurogenesis and neuronal migration. Loss of Flna in neural progenitor cells (NPCs) led RGs to unde… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
21
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(25 citation statements)
references
References 51 publications
4
21
0
Order By: Relevance
“…Double mutant mice (Flna flox/y; Emx1Cre+ ; Flnb -/-) reveals periventricular nodules, variable in size, number and distribution, present in both cerebral hemispheres, and containing mixed neurons and glia cells. Mouse phenotypes were consistent with radiological and pathological studies in FLNA patients, and suggested that PVH caused by Flna loss is a condition in which additional neurons are generated without compromising production and migration of neurons destined for the neocortex [200]. Indeed, this work demonstrated that the Flna-phenotype primarily results from an increased neurogenesis of mislocalized IPs present in the periventricular space.…”
Section: 23b Animal Models and Functional Studiessupporting
confidence: 80%
See 2 more Smart Citations
“…Double mutant mice (Flna flox/y; Emx1Cre+ ; Flnb -/-) reveals periventricular nodules, variable in size, number and distribution, present in both cerebral hemispheres, and containing mixed neurons and glia cells. Mouse phenotypes were consistent with radiological and pathological studies in FLNA patients, and suggested that PVH caused by Flna loss is a condition in which additional neurons are generated without compromising production and migration of neurons destined for the neocortex [200]. Indeed, this work demonstrated that the Flna-phenotype primarily results from an increased neurogenesis of mislocalized IPs present in the periventricular space.…”
Section: 23b Animal Models and Functional Studiessupporting
confidence: 80%
“…A recent study in the mouse developing cortex showed however, that conditional deletion of Flna in neuronal progenitor cells highly resembles PVH in humans [200]. Loss of the mitogenactivated protein kinase kinase kinase 4 (Mekk4 or Map3K4) in mice, a regulator of FlnA phosphorylation, leads to a similar phenotype [201].…”
Section: 23b Animal Models and Functional Studiesmentioning
confidence: 99%
See 1 more Smart Citation
“…While FlnA loss in mice impairs neural migration, it does not lead to PH formation, suggesting that FlnA loss might be essential for cell motility but not sufficient for PH formation in mice. Additive loss of FlnB with FlnA, however, does lead to PH in mice but has been proposed to be due to changes in proliferation from interactions between progenitors and the vasculature (Houlihan et al 2016). Our studies have also suggested that loss of FlnA alone or in combination with Fmn2 leads to microcephaly in mice, with the impairment in progenitor proliferation due to vesicle trafficking defects (Lian et al 2012(Lian et al , 2016.…”
Section: Discussionmentioning
confidence: 51%
“…Klaus et al (2019) went on to show defective RG morphologies and transcriptional signatures, a discontinuous apical surface and slowed migration in human in vitro organoid models (Klaus et al, 2019). RG delamination most probably due to perturbed apical adhesion or signaling was Actin-binding protein making a link with plasma membrane proteins Fox et al, 1998;Feng et al, 2006;Houlihan et al, 2016 GNAI2/ Gnai2 Hong et al, 2005;Wang et al, 2006;Caro-Llopis et al, 2016 (Continued) Frontiers in Cell and Developmental Biology | www.frontiersin.org also observed in these and other models (e.g., also with EML1 mutations giving rise to SH, Kielar et al, 2014) and this can lead to subtle or severe disruption of the ventricular surface, sometimes resulting in heterotopia. Several PH proteins (e.g., GNAI2, GSPM2 involved in G-protein signaling) are likely to be involved in the transduction of extracellular signals to intracellular effectors (Lee et al, 2006;Hamada et al, 2017).…”
Section: Apically Disrupted Rgsmentioning
confidence: 99%